Praktik Cooperative Learning Berbasis Kearifan Lokal Dalam Meningkatkan Literasi Numerasi Disekolah Dasar - Syahriani Sirait; Anim Anim; Rina Hayati; Andy Sapta; Saputri Widya (STMIK Royal, 2022)
Abstract: Monotonous learning in elementary schools, teachers do not use a learning model to improve numeracy literacy in elementary schools. To overcome this problem, namely by using a cooperative learning model. Cooperative learning model is a learning model in which students learn and work in small groups collaboratively with 4-5 members with heterogeneous group structures. This service aims to find out how to improve the application of cooperative learning models based on local wisdom in elementary schools in order to increase numeracy literacy. This method is a participatory action study, namely the implementation of the method by considering the existence of a problem study stage by involving students in elementary schools, as well as looking for the most appropriate alternative solution in overcoming the problem. The result of this service is students' understanding of the cooperative learning model which can be seen from discussions and questions and answers. In addition, the results of this service increase students' ability to work together to improve numeracy literacy.Keywords: cooperative learning; local wisdom; numerical literacy Abstrak: Pembelajaran di Sekolah Dasar yang monoton, guru tidak menggunakan sebuah model pembelajaran untuk meningkatkan literasi numerasi di Sekolah Dasar. Untuk mengatasi masalah tersebut yakni dengan menggunakan model cooperative learning. Model cooperative learning adalah suatu model pembelajaran dimana siswa belajar dan bekerja dalam kelompok kecil secara kolaboratif yang anggotanya 4–5 orang dengan struktur kelompok heterogen. Pengabdian ini bertujuan untuk mengetahui bagaimana meningkatkan penerapan model pembelajaran kooperatif berbasis kearifan lokal di sekolah dasar dalam rangka peningkatan literasi numerasi. Metode ini yaitu kaji tindak partisipatif yaitu pengimplementasian metode dengan mempertimbangkan adanya tahap kajian masalah dengan melibatkan siswa di Sekolah Dasar, serta mencari alternatif solusi yang paling tepat dalam mengatasi permasalahan. Hasil dari pengabdian ini adalah pemahaman siswa mengenai model pembelajaran Cooperative Learning yang dapat dilihat dari diskusi dan tanya jawab. Selain itu hasil dari pengabdian ini menambah kemampuan siswa dalam bekerja sama untuk meningkatkan literasi numerasi.Kata Kunci : cooperative learning; kearifan lokal; literasi numerasi